Modelling of fin width dependent threshold voltage in fin shaped nano channel AlGaN/GaN HEMT. (May 2020) - Chakrabarty, A.; Swain, R.
Abstract: A systematic theoretical model of threshold voltage ( V T ) for AlGaN/GaN fin shaped nano channel HEMT (FinHEMT) structure has been proposed. This device can achieve enhancement mode operation with decreased fin width ( W fin ). This proposed model captures the decreased two dimensional electron gas ( 2DEG ) density due to combined effect of built-in partial strain relaxation and partial side wall depletion ( W depl ) of nano channel due to surface potential of sidewalls. This leads to positive V T which varies inversely with W fin . This influence indicates that narrower fin width below 60 nm contributes to a stable positive threshold voltage. Highlights: Compact model for VT of a normally-off Fin shaped nanostructure AlGaN/GaN HEMT is developed. The developed model outcomes are compared with existing experimental values from literature. Threshold voltage of 0.8V is obtained with 60 nm Fin width. A thin Fin width and suitable Al mole fraction play important role for achieving normally-off operation.